2012
DOI: 10.1021/jm300434z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Acquired Proteasome Inhibitor Resistance

Abstract: The development of proteasome inhibitors (PIs) has transformed the treatment of multiple myeloma and mantle cell lymphoma. To date, two PIs have been FDA approved, the boronate peptide bortezomib and, most recently, the epoxyketone peptide carfilzomib. However, intrinsic and acquired resistance to PIs, for which the underlying mechanisms are poorly understood, may limit their efficacy. In this perspective, we discuss recent advances in the molecular understanding of PI resistance through acquired bortezomib re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 63 publications
0
71
0
1
Order By: Relevance
“…In fact, Met45 has been characterized to undergo conformational changes upon binding of bortezomib (Groll et al, 2006a) or immunoproteasome inhibitor ONX 0914 (Huber et al, 2012) to the b 5 active site binding pocket. Within the S1 pocket, Met45 facilitates favorable hydrophobic interactions with the P1 side chain of salinosporamide A (Groll et al, 2006b;Kale and Moore, 2012). Hence, Met45 mutations may impact these interactions by restricting Activity and Resistance to Salinosporamide A in Leukemia salinosporamide A binding, thus conferring resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Met45 has been characterized to undergo conformational changes upon binding of bortezomib (Groll et al, 2006a) or immunoproteasome inhibitor ONX 0914 (Huber et al, 2012) to the b 5 active site binding pocket. Within the S1 pocket, Met45 facilitates favorable hydrophobic interactions with the P1 side chain of salinosporamide A (Groll et al, 2006b;Kale and Moore, 2012). Hence, Met45 mutations may impact these interactions by restricting Activity and Resistance to Salinosporamide A in Leukemia salinosporamide A binding, thus conferring resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We, as well as others, have previously reported that chronic exposure of leukemic cells to proteasome inhibitors induces acquired drug resistance (Oerlemans et al, 2008;Franke et al, 2012;Niewerth et al, 2014b). Given that actinomycete S. tropica harbors intrinsic resistance to salinosporamide A by a similar mechanism as acquired resistance to proteasome inhibitors including bortezomib in leukemic cells (Kale and Moore, 2012), we set out to explore the acquisition of resistance to salinosporamide A in cultured CEM leukemic cells by stepwise gradual increments. Resistance emerged gradually over a period of 6 months with CEM cells adapting to growth in the presence of 20 nM salinosporamide A (CEM/S20).…”
Section: Sensitivity Of Bortezomib-sensitive and -Resistantmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cell culture models of acquired resistance often accumulate mutations in the catalytic subunits of the 20S proteasome (11,12). In terms of clinical relevance, however, such mutations have yet to be detected in clinical samples (13).…”
mentioning
confidence: 99%
“…Several studies indicate that overexpression of catalytic subunits is the primary cellular response mechanism to BTZ treatment and may precede acquisition of β5 mutations (Franke et al , 2012; Niewerth et al , 2013), as well as increased β2 and β1 activity (Ruckrich et al , 2009). Given that both pan‐proteasome inhibitory activity (Britton et al , 2009) and irreversible binding to the proteasome subunits (Orlowski, 2013; Dou & Zonder, 2014) have been postulated to overcome BTZ resistance and provide prolonged activity, the unique pharmacological profile of MRZ may confer therapeutic advantage by irreversibly inhibiting more than one proteasomal activity (reviewed in Kale & Moore, 2012). …”
mentioning
confidence: 99%